Dual Therapy Deflazacort/Doxycyclyne Is Better Than Deflazacort Monotherapy to Alleviate Cardiomyopathy in Dystrophin-Deficient mdx Mice. (September 2017) - Pereira, Juliano Alves; Mauricio, Adriana Fogagnolo; Marques, Maria Julia; Neto, Humberto Santo
Cardiomyopathy related to the absence of dystrophin is an important feature in Duchenne muscular dystrophy (DMD) and in the mdx mouse. Doxycycline (DOX) could be a potential therapy for mdx skeletal muscles dystrophy. We investigated whether the corticoid deflazacort (DFZ) plus DOX could improve cardiac mdx dystrophy better than DFZ alone, later (17 months) in dystrophy. Mdx mice (8 months old) received DFZ/DOX or DFZ for 9 months. The combined therapy was greater than DFZ in reducing fibrosis (60% decrease with DFZ/DOX and 40% with DFZ alone) in the right ventricle and transforming growth factor β levels (6.8 ± 3.2 in untreated mdx mice, 2.8 ± 1.4 in combined therapy, and 4.6 ± 1.7 in DFZ; P < .05). Combined therapy more effectively ameliorated cardiac dysfunction (electrocardiogram [ECG]) than DFZ. Improvements were seen in the cardiomyopathy index (0.8 ± 0.1 in combined therapy and 1.0 ± 0.2 in DFZ), heart rate (418 ± 46 bpm in combined therapy and 457 ± 29 bpm in DFZ), QRS interval (11.3 ± 2 in combined therapy and 13.6 ± 1 in DFZ), and Q wave amplitude (−40.7 ± 21 in combined therapy and −90.9 ± 36 in DFZ). Both therapies decreased markers of inflammation (tumor necrosis factor α, nuclear factor κB, and metalloproteinase 9). DFZ/DOX improved mdx cardiomyopathy at this stage of the disease, supporting further clinical investigations.